Prevention of Tachycardic Action of Hydralazine - Songkittiguna, Prasert; Jindagul, Giatibungon (Journal of Basic and Applied Pharmacology, 2015)
The hypotensive action of hydralazine (0.5-2 mg/kg) was enhanced by pretreatment of normotensive anesthetized rats with the drugs: haloperidol (0.21 mg/kg), indomethacin (3 mg/kg) and atropine (0.5 mg/kg) The corresponding tachycardia produced by hydralazine was abolished by haloperido/ or indomethacin or atropine. The hypotensive potentiation of the drugs with hydralazine is worth studying.